Mastering cyber intelligence gain comprehensive knowledge and skills to conduct threat intelligence for effective system defense - Dahj, Jean Nestor M. (Packt Publishing, Limited, 2022)
Develop the analytical skills to effectively safeguard your organization by enhancing defense mechanisms, and become a proficient threat intelligence analyst to help strategic teams in making informed decisions Key Features Build the analytics skills and practices you need for analyzing, detecting, and preventing cyber threats Learn how to perform intrusion analysis using the cyber threat intelligence (CTI) process Integrate threat intelligence into your current security infrastructure for enhanced protection Book Description The sophistication of cyber threats, such as ransomware, advanced phishing campaigns, zero-day vulnerability attacks, and advanced persistent threats (APTs), is pushing organizations and individuals to change strategies for reliable system protection. Cyber Threat Intelligence converts threat information into evidence-based intelligence that uncovers adversaries' intents, motives, and capabilities for effective defense against all kinds of threats. This book thoroughly covers the concepts and practices required to develop and drive threat intelligence programs, detailing the tasks involved in each step of the CTI lifecycle. You'll be able to plan a threat intelligence program by understanding and collecting the requirements, setting up the team, and exploring the intelligence frameworks. You'll also learn how and from where to collect intelligence data for your program, considering your organization level. With the help of practical examples, this book will help you get to grips with threat data processing and analysis. And finally, you'll be well-versed with writing tactical, technical, and strategic intelligence reports and sharing them with the community. By the end of this book, you'll have acquired the knowledge and skills required to drive threat intelligence operations from planning to dissemination phases, protect your organization, and help in critical defense decisions. What you will learn Understand the CTI lifecycle which makes the foundation of the study Form a CTI team and position it in the security stack Explore CTI frameworks, platforms, and their use in the program Integrate CTI in small, medium, and large enterprises Discover intelligence data sources and feeds Perform threat modelling and adversary and threat analysis Find out what Indicators of Compromise (IoCs) are and apply the pyramid of pain in threat detection Get to grips with writing intelligence reports and sharing intelligence Who this book is for This book is for security professionals, researchers, and individuals who want to gain profound knowledge of cyber threat intelligence and discover techniques to prevent varying types of cyber threats. Basic knowledge of cybersecurity and network fundamentals is required to get the most out of this book.